Comparative Test Of Effectiveness Between Lotus (Nymphaea Firecrest) And Water Hyacinth (Eichhornia Crassipes) To Reduce Tofu Wastewater Pollutants - Muliyadi Muliyadi (poltekkes kemenkes mataram, 2020)
Tofu industrial liquid waste is waste generated in the process of making tofu or when washing soybeans. In Ternate City, North Maluku, tofu waste is generally discharged into the sea; this causes environmental pollution. This study aims to compare the effectiveness of lotus (Nymphaea Firecrest) and water hyacinth (Eichhornia Crassipes) to reduce levels of pollutants TDS (Total Dissolved Solids) and TSS (Total Suspended Solid) in tofu wastewater in the Tofu Industry in Jambula Village by